Komunikasi Korporat Industri Halal dalam Membangun Citra Positif Secara Berkelanjutan Melalui Media Sosial - Rohimah, Afifatur; Fikri Zuhriyah, Luluk; Jupriono (Journal of Islamic Communication Studies, 2023)
Corporate communication is the key to success in building a positive image in the new media era. Moreover, Social media has an important role in contributing to the performance of public relations in all business sectors, including the halal industry. KOMPHI (the Indonesian halal product lovers community) is one of the real proofs that the halal industry is trying to build a positive image on an ongoing basis. The use of social media such as Instagram and TikTok is the key to success in achieving a positive image. This study uses descriptive and qualitative methods to explore the use of social media to build a sustainable, positive image. Interviews, literature studies, and documentation are data collection methods that are considered relevant. The results show that new media theory plays an important role in accelerating the process of achieving a sustainable positive image. Social media is not only a publication and engagement medium for users and followers. Social media also plays an important role in maintaining the existence of a brand. Social media also plays a role in creating new sub-businesses through content production. Therefore, new media, such as social media, play a very important role in shaping a positive image while maintaining a sustainable positive image.